Factors and Practices Associated with Self-Medicating Children among Mexican Parents - Angel Josabad Alonso-Castro; Yeniley Ruiz-Noa; Gissela Cristel Martínez-de la Cruz; Marco Antonio Ramírez-Morales; Martha Alicia Deveze-Álvarez; Raymundo Escutia-Gutiérrez; Candy Carranza-Álvarez; Fabiola Domínguez; Juan José Maldonado-Miranda; Alan Joel Ruiz-Padilla (MDPI AG, 2022)
Background: Pediatric self-medication is based on the subjective interpretation of symptoms in children by the mother or an adult, the decision to self-medicate is made by a third party. The objective of this work is to provide information on the factors and practices associated with the self-medication of children among parents in Mexico. Methods: A cross-sectional and descriptive study was conducted between June 2020 and December 2021 on Mexican parents with children under 12 years of age. Online questionnaires were completed with sections on sociodemographic characteristics, use of medicines or medicinal plants and their treated symptoms, sources of collection, and their recommendation. Results: A total of 9905 online surveys were completed with representation from the 32 states of Mexico, and the prevalence of self-medication was 49.6% (n = 4908). Associated factors were age, having two or more children, children with chronic illnesses, medium educational level, unemployment or employment unrelated to health, medium and high socioeconomic level, and lack of medical security. Respondents self-medicated their children on the recommendation of a family member or friend (55.8%), and own initiative (28%). The most used medication was VapoRub (61.3%), followed by paracetamol (56.9%) and chamomile (33.1%), and the most prevalent symptoms were flu/flow (47.7%) followed by cough (34.2%). The main reasons were perceiving symptoms as not serious (69.9%) and reusing medications (51.9%). Conclusions: There is a high prevalence of self-medication in children in Mexico, mainly associated with children with chronic diseases and families with three or more children.